Adolescent Self-Disclosure in the Context of Interpersonal Relationships in the Digital Era - Kadek Nanda Osyana Putri Putri; Ni made Prasiwi Bestari (Edusoshum : Journal of Islamic Education and Social Humanities, 2025)
The increase in the use of digital media by adolescents, which affects the way they express themselves and form social bonds, is a key driver of this study. The topic studied was the extent to which adolescent self-disclosure on social media affects interpersonal communication in the digital age. The purpose of this study is to understand the forms, factors, and impact of adolescent self-disclosure in digital interactions. Eight adolescents between the ages of 18 and 24 and a communication expert from the city of Denpasar participated in a qualitative study using phenomenological methods. In-depth interviews, observations, and documentation studies were used to collect data. Research shows that teens selectively disclose personal information by considering the boundaries of privacy, emotional closeness, and trust.  Self-disclosure helps increase interpersonal trust and foster positive social relationships. In conclusion, adolescent self-disclosure in the digital era is a form of adaptation of modern interpersonal communication that emphasizes the balance between social obligations, self-expression, and self-control.